Flavonoids activate pregnane × receptor-mediated CYP3A4 gene expression by inhibiting cyclin-dependent kinases in HepG2 liver carcinoma cells - Dong, Hanqing (BioMed Central, 2010)
BACKGROUND: The expression of the drug-metabolizing enzyme cytochrome P450 3A4 (CYP3A4) is regulated by the pregnane × receptor (PXR), which is modulated by numerous signaling pathways, including the cyclin-dependent kinase (Cdk) pathway. Flavonoids, commonly consumed by humans as dietary constituents, have been shown to modulate various signaling pathways (e.g., inhibiting Cdks). Flavonoids have also been shown to induce CYPs expression, but the underlying mechanism of action is unknown. Here, we report the mechanism responsible for flavonoid-mediated PXR activation and CYP expression. RESULTS: In a cell-based screen designed to identify compounds that activate PXR-mediated CYP3A4 gene expression in HepG2 human carcinoma cells, we identified several flavonoids, such as luteolin and apigenin, as PXR activators. The flavonoids did not directly bind to PXR, suggesting that an alternative mechanism may be responsible for flavonoid-mediated PXR activation. Consistent with the Cdk5-inhibitory effect of flavonoids, Cdk5 and p35 (a non-cyclin regulatory subunit required to activate Cdk5) were expressed in HepG2. The activation of Cdk5 attenuated PXR-mediated CYP3A4 expression whereas its downregulation enhanced it. The Cdk5-mediated downregulation of CYP3A4 promoter activity was restored by flavonoids, suggesting that flavonoids activate PXR by inactivating Cdk5. In vitro kinase assays showed that Cdk5 directly phosphorylates PXR. The Cdk kinase profiling assay showed that apigenin inhibits multiple Cdks, suggesting that several Cdks may be involved in activation of PXR by flavonoids. CONCLUSIONS: Our results for the first time link the stimulatory effect of flavonoids on CYP expression to their inhibitory effect on Cdks, through a PXR-mediated mechanism. These results may have important implications on the pharmacokinetics of drugs co-administered with herbal remedy and herbal-drug interactions.